Self-Reflection as a Tool for the Formation of Information Culture Foundations of Preschool Children - Abitova, Gulbanu T.; Bapayeva, Mariyam K.; Ermekbaeva, Laura K.; Utepbergenova, Zeynekul D. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The study aims to clarify the essential and urgent socio-pedagogical problem of preparing the young generation for life in the actively developing information society. Background: At preschool age, the elements of information reflection are expressed in the ability to flexibly respond to information changes and the ability to reason and comprehend the conditions and results of cognitive activity. The most important requirement in the formation of self-reflection of a preschooler is a critical attitude to information which begins with obtaining the information and ends with the adoption of a conscious decision, the formation of one’s own attitude. Method: The primary method of research in the article is the study of literature on the research problem, and a method of analysis, which allowed to assert that self-reflection is an important element of information culture of a preschooler. Results: The authors singled out and described, pedagogical conditions of formation of foundations of information culture of children of senior preschool age directed at the creation of the developing information and cultural environment as communicative and creative space in preschool educational establishment; substantiation of cognitive interest as a fundamental component of stimulating creative and search initiatives of a child; orientation to the personally significant attitude of a preschooler to the process of formation of the information culture foundations. Conclusion: The research conducted by the authors allowed to assert that self-reflection is an essential element of the information culture of a preschooler.